Efficacy of Transversus Abdominis Plane Block After Post Caesarean Section Delivery - Singh, Grisuna; Banu, Farhat; Haque, Husneyera (Journal of Nepalgunj Medical College, 2018)
Introduction: Post operative pain following caesarean section delivery can negatively affect early wound healing, proper breast feeding to the new born baby and therefore impair mother to child bonding. Combination of non steroidal anti inflammatory drugs (NSAIDS) and opioids has most commonly been used in pain management. The combination of regional anesthetic techniques like Transversus Abdominis Plane (TAP) block reduces pain and the dose of total analgesics consumed and therefore helps to prevent opioid related side effects. Objective: To evaluate the analgesic efficacy of Transversus Abdominis Plane block for management of postoperative pain in the first 24 hours after caesarean section. Methodology: It is a prospective randomized controlled single blinded study involving 60 patients of ASA II done in Nepalgunj Medical College Teaching Hospital over a period of 2 months. They are divided into two groups of 30 patients each. Group 1 received 20 ml of 0.25% isobaric bupivacaine in the triangle of Petit bilaterally. Group 2 received IV analgesics (NSAIDS and Tramadol 50 mg with Phenargan 25 mg). VAS score was taken every 6 hourly for 24 hours post operatively. Results: The mean VAS score of the patients in group 2 at 0-6 hours, 6-12 hours, 12-18 hours and 18-24 hours was 6.73(SD±0.69), 6.63(SD±0.610), 6.40(SD±0.56) and 6.43(SD±0.57) respectively. The mean VAS score of the patients who received block is significantly less as compared to those who did not receive the block with a p value of <0.001. The mean time to first analgesic request in group 1 was 10.83(SD±2.95) and in group 2 was 4.87(SD±0.68) with a p value of <0.001. In group 1, 70% patients received single dose of analgesics, 23.3% received two doses and 6.7% received three doses of analgesics. In group 2 all the patients received four doses of analgesics. Conclusion: Transversus Abdominis Plane Block can be used as a part of multimodal analgesic therapy for the management of post operative pain after caesarean section as it is technically less demanding, safe and economical. It reduces the side effects related with opioid analgesics and encourage early mobility, wound healing and proper mother to child bonding.